In Vivo Susceptibility of Cryptococcus neoformans to Hamycin, Amphotericin B, and 5-Fluorocytosine - Shadomy, Smith (1970)
Previous investigations have shown that hamycin is 5 to 10 times more active in vitro than amphotericin B against Cryptococcus neoformans, whereas 5-fluorocytosine is approximately 15 times less active. Present studies are concerned with a comparison of these drugs in vivo. Three strains of C. neoformans which varied in both their virulence for mice and their susceptibilities to the antifungal agents were studied. Acute experimental infections were established in mice by using inocula containing approximately 4 × 10(6) cells. The mice were treated by gastric intubation for 28 days; daily dosages of the three drugs ranged from 12.5 to 250 mg/kg. The polyenes were suspended in 5% dimethyl sulfoxide, whereas 5-fluorocytosine was suspended in saline. Amphotericin B was the most effective drug, with almost complete absence of toxic deaths in control mice and increased survival in mice infected with two of the three strains and treated with 25 mg/kg per day or more. 5-Fluorocytosine was nontoxic but provided protection against only one strain. Hamycin was both the least effective and the most toxic compound, providing only slight protection at doses of 12.5 or 25 mg/kg per day and causing toxic deaths in over 50% of uninfected mice at doses above 25 mg/kg per day.